Mission driven : the path to a life of purpose - Hayes, Mike (Former Commanding Officer of Seal Team Two) (Grand Central Publishing, 2025)
Former Navy SEAL commander, White House Fellow, and nonprofit and business leader Mike Hayes offers an inspiring playbook for understanding and achieving your most rewarding and purposeful life.Mission Driven offers a practical guide for transition points: young people, recent graduates, professionals shifting to new roles, or people shifting to find new balance in their lives. It is divided into two sections: The Long Game (figuring out who you want to be, how you define success, and what kind of impact you're looking to have in your own life and the world) and The Short Game (moving readers from the who to the how, taking the learnings they've gathered in the first half of the book and applying them toward building their lives and finding their next great opportunities).